Use of InfoWorks River Simulation (RS) in Sungai Sarawak Kanan Modeling - Mah, D.Y.S.; Putuhena, F.J.; Salim, Said (The Institution of Engineers, Malaysia, 2007)
The main purpose of this project was to reconstruct historical flood events at the flood-prone Sungai Sarawak Kanan to obtain flood hydrographs to provide explanation to the flooding of Bau town and surrounding areas. The Sungai Sarawak Kanan and its floodplains were modeled using one-dimensional hydrodynamic modeling approach, by utilising the Wallingford Software model - InfoWorks River Simulation (RS), coupled with its embedded GIS applications, to capture the hydraulic response of the river and its floodplains in extreme flooding conditions. InfoWorks RS was applied on 23 km of Sungai Sarawak Kanan between Buan Bidi and Siniawan. The model was calibrated with 3 storm events, verified with another 2 sets of storm data and applied on reconstructing 2 extreme events of February 2003 and January 2004 floods where the correlation of observed and simulated data at Siniawan were between 0.87 – 0.98. The differences of observed and modeled peak water levels were within the allowable limit of ± 0.10 m. Similar efficiency had been achieved in the interpretation on the simulation of reconstruction results through analysis of flood depths and flood watermarks. The model was managed to estimate the flood depths and flood watermarks within the observation range by Department of Irrigation and Drainage Sarawak. This shown that InfoWorks RS is an appropriate model for flood modeling in Sungai Sarawak Kanan.